Pengaruh Kemampuan Kerja dan Loyalitas terhadap Kinerja Pegawai yang Dimediasi oleh Promosi Jabatan: (Studi pada pegawai PT. Pegadaian CP Ponorogo) - Agatha Tyagita Ayuningtyas; Chamariyah Chamariyah; Indra Prasetyo (Universitas 45 Surabaya, 2025)
Agatha Tyagita Ayuningtyas, 2025. The Influence of Work Ability and Loyalty on Employee Performance Mediated by Job Promotion (Study on Employees of PT. Pegadaian CP Ponorogo). Postgraduate Program, Wijaya Putra Surabaya University. This study is an associative or causal relationship research with a quantitative approach, using a sample of 46 respondents. Data analysis is conducted using SEM-PLS (Structural Equation Modeling - Partial Least Squares). The objectives of the study are: 1) To test and analyze whether work ability affects employee promotion; 2) To test and analyze whether loyalty affects employee promotion; 3) To test and analyze whether job promotion affects employee performance; 4) To test and analyze whether work ability indirectly affects employee performance through job promotion. The results of the study show that: 1) Work ability has a direct and significant effect on job promotion, with an original sample value of 0.272; 2) Loyalty has a direct and significant effect on job promotion, with an original sample value of 0.311; 3) Job promotion has a direct and significant effect on employee performance, with an original sample value of 0.643; 4) Work ability has an indirect and significant effect on employee performance mediated by job promotion, with an original sample value of 0.200. This study highlights the importance of work ability and loyalty as key factors influencing employee performance, directly and indirectly, through job promotion, providing valuable insights for human resource management at PT. Pegadaian CP Ponorogo.